THE THE EFFECT OF USING CARD SORT STRATEGY IN TEACHING VOCABULARY AT THE EIGHT GRADE OF SMP NEGERI 2 ANGKOLA SELATAN - Sri Sunarti Gulo (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Gulo, sri sunarti. 2020. The Effect of using card sort strategy in teaching vocabulary at eighth grade of SMP negeri 2 angkola selatan in 2020/2021 Academic Year) . A Skripsi, English Department Program. Institut Pendidikan Tapanuli Selatan (IPTS). The purpose of this research are to find out: 1) The application of card sort strategy in teaching vocabulary. 2) Students’ vocabulary mastery before and after using card sort strategy. 3) Whether there is a significant effect of using card sort strategy at the eighth grade of SMP negeri 2 angkola selatan. Method of the research is experimental. The population of this research are all of the eighth grade of SMP negeri 2 angkola selatan that consists of 100 students. Random sampling is used to get the sample of research , the sample consist of 33 students. The technique for collecting data are observation sheet and test. The result of the application of card sort strategy is 3.5 categorized “Very Good”. Before using card sort strategy is 26,94 categorized “Fail”. Meanwhile, after using card sort strategy is 68,21 categorized “Enough”. The result of ttest by use pair sample ttest is The value of Sig. (2-tailed) was greater than significant level (0.000<0.05). it means that there is a significant effect of using card sort strategy in teaching vocabulary at the eighth grade of SMP negeri 2 angkola selatan. Keyword: Card sort strategy, Vocabulary